Gains from Foreign Direct Investment : Macro and Micro Approaches - Alfaro, Laura (Published by Oxford University Press on behalf of the World Bank, 2019)
This paper discusses the importance of an “integrated approach” to the study of the effects of FDI on host countries. Macro-level work that examines countries at different stages of development and institutional capacity is needed to surface the role of local conditions and absorptive capacities; micro-level work, that is firm-level data in developed as well as developing nations, to understand the mechanisms that impart substance to the anticipated benefits; and theoretical work to guide the analyses. The paper summarizes likely motives for foreign direct investment and potential effects of FDI on local economies as well as recent findings from the macro literature on the role of complementarities between FDI and local policies, conditions, and institutions and summarizes new efforts to understand the micro mechanisms and channels by which host countries can benefit from multinational activity, within and between firm productivity increases.